1999
DOI: 10.1046/j.1365-280x.1999.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Paracoccidioides brasiliensis isolates can be correlated to groups defined by random amplified polymorphic DNA analysis

Abstract: Fifteen Paracoccidioides brasiliensis isolates were discriminated by the RAPD analysis into two groups with only 17% of genomic identity. The ability of P. brasiliensis isolates to invade tissues was studied in an experimental model using susceptible B10.A mice. The analysis was performed according to the severity of the lesions including the number and size of the granuloma, the number and dissemination of fungi to different organs. The isolates from two RAPD groups demonstrated a marked difference in their v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 10 publications
3
33
1
Order By: Relevance
“…Previous RAPD analyses [50][51][52], RFLP [53], and partial sequences of some genes [54,55] from several P. brasiliensis isolates, revealed genetic variability and clusters correlated with geography [50,53] or virulence [51,56]. Based on phylogenetic analysis of 65 P. brasiliensis isolates, Matute et al [57] recently proposed three distinct phylogenetic species within P. brasiliensis: S1 (a paraphyletic group formed by 38 isolates of Argentinean, Brazilian, Peruvian and Venezuelan origins, plus an isolate from an Antarctic penguin), PS2 (six isolates, five of them of Brazilian origin, and one Venezuelan) and PS3 (21 Colombian isolates).…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…Previous RAPD analyses [50][51][52], RFLP [53], and partial sequences of some genes [54,55] from several P. brasiliensis isolates, revealed genetic variability and clusters correlated with geography [50,53] or virulence [51,56]. Based on phylogenetic analysis of 65 P. brasiliensis isolates, Matute et al [57] recently proposed three distinct phylogenetic species within P. brasiliensis: S1 (a paraphyletic group formed by 38 isolates of Argentinean, Brazilian, Peruvian and Venezuelan origins, plus an isolate from an Antarctic penguin), PS2 (six isolates, five of them of Brazilian origin, and one Venezuelan) and PS3 (21 Colombian isolates).…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…Calcagno et al (1998) demonstrated that genetic variations could be associated with geographical regions but not with different clinical manifestations of paracoccidioidomycosis. However, Molinari-Madlum et al (1999) showed that RAPD profiles could be correlated with the degree of virulence of the P. brasiliensis isolates. Our results support the hypothesis that there is an influence of in vitro subculturing on the genotype of P. brasiliensis.…”
Section: Resultsmentioning
confidence: 99%
“…Random primers have been refined so that they can be used to distinguish and characterize genetic diversity among isolates of P. brasiliensis (Molinari-Madlum et al, 1999;Soares et al, 1995;Motta et al, 2002) and could differentiate the fungus based on virulence (Kurokawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that a molecular analysis would be necessary in order to better characterize and identify this fungus 5 . Recently, several papers have shown the use of molecular biology techniques to analyze the genomic variation of fungal different taxonomical levels 1,2,7,8,10 .…”
Section: Moore (1935) Identified a New Species Of Fungus Which He Namedmentioning
confidence: 99%
“…It is based on the sensitive PCR technique, but with the advantage of requiring simpler procedures, due to the use of arbitrary primers and no "a priori" knowledge of target DNA sequences 8,14,16 . This technique has been useful to discriminate isolates of fungus, such as Histoplasma capsulatum and Paracoccidioides brasiliensis 1,8,10,14 . In the present investigation we used the RAPD technique to characterize the genetic affiliation between Paracoccidioides brasiliensis and Paracoccidioides cerebriformis strains.…”
Section: Moore (1935) Identified a New Species Of Fungus Which He Namedmentioning
confidence: 99%